Pengaruh Profesionalisme Guru Terhadap Peningkatan Prestasi Belajar Siswa Kelas X Di Madrasah Aliyah Muhammadiyah 02 Pondok Modern Paciran Lamongan - Himmatul Husniyah (Jurnal Pendidikan Islam, 2021)
This study aims to identify teacher professionalism towards the improvement of student achievement in class X at Madrasah Aliyah Muhammadiyah 02 Pondok Modern PaciranLamongan. The hypothesis proposed is "there is an effect of teacher professionalism on the improvement of student achievement in class X students at Madrasah Aliyah Muhammadiyah 02 Pondok Modern PaciranLamongan". To test the correctness of the instrument hypothesis in the form of a questionnaire distributed to 10 professional teachers and 30 class X students, the proposed analysis model is Karl Pearson Product Moment Correlation at a significance level of a = 0.05 for hypothesis I and the Coefficient Determinations formula for hypothesis II. From theanalysis it is known that the Professionalism of Class X Student Teachers at Madrasah Aliyah Muhammadiyah 02 Pondok Modern PaciranLamongan is in the "good enough" category. This is evidenced by the response of the largest respondents at intervals of 21-30 as many as 3 respondents (60%), and the increase in student achievement of Class X students at Madrasah Aliyah Muhammadiyah 02 Pondok Modern PaciranLamongan in the "good enough" category.This conclusion is evidenced by the responses of the largest respondents at the interval 21-30, namely 16 respondents (53.3%). While the results of the latest research state that teacher professionalism has a positive effect on the improvement of student achievement in class X class students at Madrasah Aliyah Muhammadiyah 02 Pondok Modern PaciranLamongan. This is evidenced by the calculated r value (0.610)> r table (0.334) at the significant level a = 0.05.Thus it can be concluded that the alternative hypothesis (Ha) I which the author proposes says "there is a significant effect of Teacher Professionalism on the Improvement of Class X Student Achievement at Madrasah Aliyah Muhammadiyah 02 Pondok Modern PaciranLamongan", is proven true or "accepted". While the magnitude of the influence of Teacher Professionalism on the Improvement of Student Achievement in Class X is less than 0.50 (50%), which is 0.3721 (37.21%), although less than 50% of the second hypothesis that the author proposes is proven tobe true or "accepted" .